Algorithmic Decision Making in Management: A Philosophical Inquiry from an Islamic Ethical Perspective - Koswara, Asep; Umi Narimawati; Bobi Kurniawan (Universitas Nahdlatul Ulama Surabaya, 2025)
The rapid diffusion of algorithmic decision making in management has reshaped how organizations evaluate employees, allocate resources, and exercise managerial authority. While such systems promise efficiency and objectivity, growing evidence shows that they also generate serious epistemological, ethical, and governance challenges. This paper aims to critically examine algorithmic decision making in management from an Islamic ethical and philosophical perspective, focusing on its epistemological, ontological, and axiological implications. Using a qualitative and conceptual research design, the study applies interpretive and normative analysis to major theories in management, artificial intelligence ethics, and Islamic moral philosophy. The results indicate that algorithmic decision making is built on epistemic assumptions that overstate objectivity, ontological ambiguities that risk displacing human moral agency, and axiological limitations that undermine justice, accountability, and human dignity. Drawing on Islamic ethical principles, particularly maqāṣid al-sharīʿah, justice (ʿadl), and trust (amanah), the study proposes a normative framework that re-centers human responsibility and ethical governance in the use of algorithmic systems. In conclusion, algorithmic decision making should be treated as a decision-support mechanism rather than an autonomous authority, and its legitimacy in management depends on its alignment with Islamic ethical values and the preservation of human moral agency.